Relationship between variability of practice and variability of execution in flat tennis service - R. Menayo; J. P. Fuentes; F. J. Moreno; R. Reina; J. A. García (Asociación Española de Ciencias del Deporte, 2010)
This study analyzes the relationship between the variability in the performance of the flat tennis service and its practice under variable conditions, taking as a starting point a predictive analysis of the instantaneous kinematic variables of the hand that holds the racket. Seventeen tennis players performed services under 8 practice conditions (rackets and balls were modified), and pre-test and post-test were carried out. The players performed 120 services with the instruction to hit the ball powerfully and maintaining maximum efficiency. Data showed that two variables related to the speed and the acceleration of the hand will predict efficacy at 57.7%: both the time variation coefficients until we reach the speed peak and the final acceleration of the hand in the Y axis. Significant differences were also obtained between some instantaneous kinematic variables measured in the pre-test and the practice series, and also negative and significant correlations between these variables and the efficacy of the services. Key Words: variability, tennis, service